Examining smoking and cessation during pregnancy among an Appalachian sample: a preliminary view - Berry Traci; Sobhan Sabera; Rai Alia; Harris Carole; Gibson Mark; Cottrell Lesley; Stanton Bonita (BMC, 2007)
Abstract Background Several transitions that a woman experiences prenatally may influence her desire or ability to discontinue smoking. This study explores the role of smoking for young, Appalachian, nulliparous pregnant women and their plans for smoking during their pregnancies. Results The reports of women and their male partners were taken from baseline interviews conducted during the first trimester of pregnancy. Cigarette smoking appeared to be more than an isolated addictive activity; rather, smoking was interwoven in women's social and personal realms, often changing as their perceptions of self changed. Women and their partners who continued to smoke appeared to be depressed, reject authority, and perceived little control over issues related to being pregnant. Conclusion These findings support the argument that standard substance use treatments and polices based on stages-of-change theories may not be effective for all individuals particularly those experiencing significant developmental changes in their lives. Greater success might be obtained from treatment programs designed to recognize the impact of these transitions as it relates to the substance use. The changing experiences of pregnant women in terms of their identity development, views of others, and their relationships have not been adequately addressed in existing cessation programs. Empirically-based interventions targeting these lifestyle characteristics may lead to increased cessation success among pregnant women.